Ecoliteracy-Based Teaching Strategies in English Language Teaching for Elementary School Students - Adam, Samsudin Hi.; Ali, Silvani Umar (JOLLT Journal of Languages and Language Teaching, 2025)
Environmental degradation, particularly in regions like Ternate, Indonesia, underscores the urgency of embedding sustainability education in early schooling. While ecoliteracy has gained global recognition, its integration into English language teaching (ELT) at the elementary level remains underexplored, especially in underrepresented contexts. This study investigates the strategies used by English teachers in Ternate to incorporate ecoliteracy into classroom practice. Adopting a qualitative case study design, data were gathered from ten teachers across five schools through interviews, observations, questionnaires, and document analysis, and analyzed thematically. Findings reveal six approaches, with three emerging as most dominant: embedding environmental themes in lessons, employing project-based learning, and modeling eco-behavioral English instructions. These strategies demonstrate how language instruction can simultaneously foster communicative competence and ecological responsibility. Beyond documenting classroom practices, the study highlights the potential of ELT as a platform for sustainability education, even in resource-limited settings. It contributes to theory by linking ecolinguistics to pedagogy, and to practice by offering context-sensitive models for ecoliteracy integration. Implications extend to teacher training, curriculum design, and education policy, underscoring the need for systematic inclusion of sustainability in ELT. Ultimately, the study positions ecoliteracy not as an enrichment but as a transformative approach that unites language learning with sustainable development.